Maqashid al-Sharia Approach of Sa’id Ramadan al-Buti in Contemporary Fatwas - Nasir, Muhammad Aiman; Harun, Muhammad Safwan; Abdul Rahman, Noor Naemah (Online Journal of Research in Islamic Studies, 2024)
This article examines the Maqāṣid al-Sharīʿah (objectives of Islamic law) approach employed by Saʿīd Ramaḍān al-Būṭī in formulating contemporary fatwas. Maqāṣid al-Sharīʿah is central to understanding the purposes of Islamic rulings and ensuring that the law serves the welfare of humanity. Al-Būṭī's method involves a nuanced understanding of maṣlaḥah within the framework of the Quran, Sunnah, Ijma’ (consensus), and Qiyas (analogical reasoning). Through this lens, al-Būṭī addresses complex modern issues, such as cosmetic surgery, organ donation, political revolution, and the implementation of Hudud punishments. The article delves into al-Būṭī’s principles, illustrating how his approach aligns with classical jurisprudence while adapting to contemporary challenges. The findings highlight the balance al-Būṭī strikes between adherence to traditional sources and the consideration of the current context, making his fatwas relevant and influential. The methodology of this study is based on a qualitative approach, combining text analysis and literature review. Primary sources, including al-Būṭī’s own works and relevant fatwas, are analyzed to understand his application of Maqāṣid al-Sharīʿah. The study also employs contextual analysis to explore how al-Būṭī adapts classical principles to contemporary issues. Comparative analysis is used to assess his approach against other classical and modern juristic perspectives, emphasizing the relevance of his fatwas in today’s world. This methodological framework allows for a comprehensive examination of al-Būṭī’s contribution to contemporary Islamic jurisprudence.